The Contribution of the Fathers of the Church in the Development of Biblical Theology. Selected Methods of Patristic Exegesis. Part One - Stanisław Pamuła (Seminare, 2022)
Contribution of the Fathers of the Church to exegesis is one of their greatest gifts to Christianity. Without a doubt, their works reflecting on the Scriptures not only include issues relevant to the development of theology but also, have a great impact on Christian Spirituality. This article is the first of two dedicated to patristic exegesis. In this part, the author made a brief introduction on the development of Christian Doctrine with particular attention to J.H. Newman’s theory on the contribution of the Fathers to theology.